Balance a cart on an edge

A one-axle cart balances on a step and is only supported by point A A on the ground. The axis is rotatably mounted at point O O . The center of gravity of the cart is at point B B .

What is the absolute value of the force F = F F= |\vec F| that must be applied at point C C to hold the cart in place? In this case, the sum of all forces and torques acting on the cart must be zero.

Compare the force F F with the weight m g mg of the cart.

The points O , A , B , O, A, B, and C C are given by the position vectors O = ( 0 0 ) , A = ( 4 3 ) , B = ( 6 8 ) , C = ( 12 9 ) . \vec O = \left( \begin{array}{c} 0 \\ 0 \end{array} \right), \quad \vec A = \left( \begin{array}{c} 4 \\ -3 \end{array} \right), \quad \vec B = \left( \begin{array}{c} -6 \\ 8 \end{array} \right), \quad \vec C = \left( \begin{array}{c} 12 \\ 9 \end{array}\right). (These numbers are given in decimeters.)

The force is larger than the weight: F > m g F > m g The force is smaller than the weigth: F < m g F < m g The force is equal to the weight: F = m g F = m g

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

The points A A , B B and C C each form, together with the origin O O , right-angled triangles whose sides are in the ratio 5 : 4 : 3 5:4:3 .

In each of the points A A , B B and C C a force acts on the car. In point B B this is the weight with F B = ( 0 , m g ) \vec F_B = (0, - m g) . The force at point A A is exerted by the edge on the wheel. Since the wheel does not transmit torque to its axis (the wheel is rotatably mounted), the force acts along the connecting line between A A and the origin. Therefore, the force vector can written as F A = ( 4 5 , 3 5 ) F A \vec F_A = (- \frac{4}{5} , \frac{3}{5} ) F_A . The force F = F C \vec F = \vec F_C force at point C C has an unknown angle α \alpha to the horizontal. Thus, the vector yields F C = ( cos α , sin α ) F C \vec F_C = (\cos \alpha, \sin \alpha) F_C .

The sum of all forces must be zero:

0 = i F i = F A + F B + F C = ( 4 5 F A 3 5 F A ) + ( 0 m g ) + ( cos α F C sin α F C ) 0 = 4 5 F A + cos α F C ( I ) m g = 3 5 F A + sin α F C ( I I ) \begin{aligned} & & 0 = \sum_i \vec F_i &= \vec F_A + \vec F_B + \vec F_C \\ & & &= \left( \begin{array}{c} - \tfrac{4}{5} F_A \\ \tfrac{3}{5} F_A \end{array} \right) + \left( \begin{array}{c} 0 \\ - m g \end{array} \right) + \left( \begin{array}{c} \cos \alpha F_C \\ \sin \alpha F_C \end{array} \right) \\ \Rightarrow & & 0 &= - \frac{4}{5} F_A + \cos \alpha F_C && (I)\\ & & m g &= \frac{3}{5} F_A + \sin \alpha F_C && (II) \end{aligned} By multiplying the first line by the factor 3/4 and adding the two lines, the unknown F A F_A can be eliminated: 3 4 ( I ) + ( I I ) = m g = ( 3 4 cos α + sin α ) F C ( I I I ) \frac{3}{4} (I) + (II) = m g = \left(\frac{3}{4} \cos \alpha + \sin \alpha \right) F_C \qquad (III)

In addition, the total torque must be zero 0 = i T i = A × F A + B × F B + C × F C = ( 4 3 0 ) × ( 4 5 F A 3 5 F A 0 ) + ( 6 8 0 ) × ( 0 m g 0 ) + ( 12 9 0 ) × ( cos α F C sin α F C 0 ) = ( 0 0 0 ) + ( 0 0 6 m g ) + ( 0 0 ( 12 sin α 9 cos α ) F C ) m g = ( 3 2 cos α 2 sin α ) F C ( I V ) \begin{aligned} & & 0 = \sum_i \vec T_i &= \vec A \times \vec F_A + \vec B \times \vec F_B + \vec C \times \vec F_C \\ & & &= \left( \begin{array}{c} 4 \\ -3 \\ 0 \end{array} \right) \times \left( \begin{array}{c} - \tfrac{4}{5} F_A \\ \tfrac{3}{5} F_A \\ 0 \end{array} \right) + \left( \begin{array}{c} -6 \\ 8 \\ 0 \end{array} \right) \times \left( \begin{array}{c} 0 \\ - m g \\ 0 \end{array} \right) + \left( \begin{array}{c} 12 \\ 9 \\ 0 \end{array} \right) \times \left( \begin{array}{c} \cos \alpha\, F_C \\ \sin \alpha \, F_C \\ 0 \end{array} \right) \\ & & &= \left( \begin{array}{c} 0 \\ 0 \\ 0 \end{array} \right) + \left( \begin{array}{c} 0 \\ 0 \\ 6 m g \end{array} \right) + \left( \begin{array}{c} 0 \\ 0 \\ (12 \sin \alpha - 9 \cos \alpha) F_C \end{array} \right)\\ \Rightarrow & & m g &= \left( \frac{3}{2} \cos \alpha - 2 \sin \alpha \right) F_C & & (IV)\end{aligned} By comparing equations (III) and (IV) we get 3 4 cos α + sin α = 3 2 cos α 2 sin α 3 sin α = 3 4 cos α tan α = sin α cos α = 1 4 α = arctan 1 4 1 4 \begin{aligned} & & \frac{3}{4} \cos \alpha + \sin \alpha &= \frac{3}{2} \cos \alpha - 2 \sin \alpha \\ \Rightarrow & & 3 \sin \alpha &= \frac{3}{4} \cos \alpha \\ \Rightarrow & & \tan \alpha &= \frac{\sin \alpha}{\cos \alpha} = \frac{1}{4} \\ \Rightarrow & & \alpha &= \arctan \frac{1}{4} \approx 14^\circ \end{aligned} Inserting the result for α \alpha in equation (III) or (IV) results F C = m g 3 4 cos α + sin α = m g 3 2 cos α 2 sin α 1.03 m g F_C = \frac{m g}{\frac{3}{4} \cos \alpha + \sin \alpha} = \frac{m g}{\frac{3}{2} \cos \alpha - 2 \sin \alpha} \approx 1.03 \cdot mg

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...